Ommatophoca rossi Gray 1844 - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Ommatophoca rossi Gray, 1844. Zool. Voy. H. M.S. "Erebus" and "Terror," 1: 3. TYPE LOCALITY: Antarctica, Ross Sea. DISTRIBUTION: Circumpolar, Antarctic pack ice, particularly King Haakon VII Sea. ISIS NUMBER: 5301413002010001001. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Carnivora, pp. 244-289 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 288, DOI: 10.5281/zenodo.7352980